Gicht und Calciumpyrophosphat-Dihydrat-Arthropathie („Pseudogicht“) – ein Update - Reuss-Borst, Monika; Tausche, Anne-Kathrin (DMW - Deutsche Medizinische Wochenschrift, 2018)
The metabolic diseases gout and calciumpyrophosphate deposition (CPPD) (formerly: chondrocalcinosis/pseudogout) are crystal arthropathies which are caused by crystals in synovial fluid and in the case of gout also in periarticular structures. Today, in particular gout is considered as an auto-inflammatory process since phagocytosis of monosodium urate crystals by monocytes/macrophages results in the activation of the innate immune system by activation of the NRLP3-Inflammasome and consecutive secretion of the key cytokine interleukin-1ß and other pro-inflammatory cytokines. The prevalence of both crystal arthropathies rises with increasing age of patients. Most often they present clinically as an acute monarthritis of different locations. Beside typical clinical presentation, performance of ultrasonography, conventional X-Ray of joints and under special circumstances dual-energy-computer tomography could be also helpful diagnostic tools. There are EULAR guidelines describing the diagnostic algorithm for making right diagnosis. The arthrocentesis with microscopic detection of crystals is established diagnostic gold standard. Whereas crystals of monosodium urate could be very clearly be seen as relatively large intra- and extracellular needles with a strong birefringence in polarized light microscopy the detection of CPPD-crystals is more difficult. Those crystals are much smaller, showing weaker birefringence and are sometimes only seen with ordinary light microscopy. As both crystal diseases are mediated by IL-1 driven processes, the therapeutic intervention first target the acute inflammation consisting in colchicine, NSAIDs and glucocorticoids. Secondarily, in gout there are well established causal therapies to lower effectively serum urate levels below the target of 6 mg/dL (360 µmol/l). Unfortunately, those causal therapeutic options are still lacking in CPPD.
Keywords: Kristallarthropathien; Gicht; Chrondrokalzinose; Calciumpyrophosphat-Arthropathie; Serumharnsäure